Reposição de cães em área endêmica para leishmaniose visceral - Andrade, Andréa Maria; Queiroz, Luzia Helena [UNESP]; Nunes, Gilson Ricardo; Perri, Silvia Helena Venturoli [UNESP]; Nunes, Caris Maroni [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2007)
Esse trabalho objetivou estimar a reposição de cães em área endêmica para leishmaniose visceral, onde a eutanásia de animais soropositivos é indicada como medida de controle, e avaliar os motivos que levaram a aquisição ou não de novos animais. Houve a reposição em 44,5% dos casos, principalmente devido à necessidade de companhia ou guarda. O principal motivo para a não-reposição foi o temor da leishmaniose visceral.

This study aimed to estimate the dog replacement rate in an area endemic for visceral leishmaniasis, in which slaughter of seropositive animals was indicated as a control measure, and to evaluate the reasons why new animals were or were not acquired. The animals were replaced in 44.5% of the cases, and this was done mainly because of the need for a companion or guard dog. The main reason for not replacing the dog was fear of visceral leishmaniasis.
Dog replacement in an area endemic for visceral leishmaniasis
Keywords: Leishmaniose visceral; Reposição canina; População canina; Visceral leishmaniasis; Canine replacement; Canine population